Ecological and social impacts of eucalyptus tree plantation on the environment - Bayle, GK (Journal of Biodiversity Conservation and Bioresource Management, 2019)
Eucalyptus is an ever green flowering tree and a shrub which belong to the family Myrtaceae, subfamily Myrotideae and consists of some 800 species. This tree is native to Australia and widely planted for various uses in the different parts of Ethiopia integrating into the various farming systems, and their planting has resulted in high economic profitability. It is over a century since eucalyptus was introduced in Ethiopia for multipurpose use and rescues the remaining indigenous forests from being destroyed, for controlling soil erosion, for replacing indigenous species for fuel-wood, thereby preventing further degradation of natural forests by quickly producing firewood, would eliminate the causes which frequently may have led to land degradation and desertification and also a food and habitat for wild animals. But, it also a harmful effect on the environment, uses a lot of nutrient which is leading to soil exhaustion and reduction of crop yields, secretion of allelochemical and decreasing crop production, but the trees are neither good nor bad, and careful analysis of the ecological and social implications should be undertaken before planting. Decisions, such as what, where, why and how to grow and how to manage it have to be made; and the social and ecological implications of each decision, as well as the economic implications, have to be weighted up. J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(1): 93-104